Comparative Outcomes of Treatment Initiation With Brand vs. Generic Warfarin in Older Patients. Issue 6 (19th January 2020) - Desai, Rishi J.; Gopalakrishnan, Chandrasekar; Dejene, Sara; Sarpatwari, Ameet S.; Levin, Raisa; Dutcher, Sarah K.; Wang, Zhong; Wittayanukorn, Sara; Franklin, Jessica M.; Gagne, Joshua J.
Abstract : The anticoagulant response to warfarin, a narrow therapeutic index drug, increases with age, which may make older patients susceptible to adverse outcomes resulting from small differences in bioavailability between generic and brand products. Using US Medicare claims linked to electronic medical records from two large hospitals in Boston, we designed a cohort study of ≥ 65‐year‐old patients. Patients were followed for a composite effectiveness outcome of ischemic stroke or venous thromboembolism, a composite safety outcome, including major hemorrhage, and a 1‐year all‐cause mortality outcome. After propensity score fine‐stratification and weighting to account for > 90 confounders, hazard ratios comparing brand vs. generic warfarin initiators (95% confidence intervals) for the effectiveness, safety, and all‐cause mortality outcomes, were 0.97 (0.65–1.46), 0.94 (0.65–1.35), and 0.84 (0.62–1.13), respectively. Results from subgroup analyses of patients with atrial fibrillation, CHADS‐VASc score ≥ 3, and HAS‐BLED score ≥ 3 were consistent with the primary analysis.